Розробка методики оцінки невизначеності вимірювань під час калібрування тахометру - Меюс, Ю. О. (ХНУРЕ, 2023)
The purpose of the work is to improve the metrological support of the measurement of the rotation frequency by developing a method of calibrating an electronic tachometer. Research methods - methods of statistical analysis of measurement information, methods of uncertainty theory. The object of the study is the uncertainty of household water meter calibrations. The processing of the results of repeated observations was carried out. The standard uncertainty according to type A, В and the total standard uncertainty are determined. Compile the measurement uncertainty budget.